Symposium 9: Towards an Evaluation Framework for Large Scale Networked Learning Initiatives - Fisher, Shelagh (Proceedings of the International Conference on Networked Learning, 2004)
The formative evaluation of the JISC’s Learning and Teaching Programme within the context of its wider Information Environment development strategy was a three year project (EDNER) funded by JISC and was completed in July 2003. This paper provides a reflection upon the strategies which were deployed in EDNER in conducting the formative evaluation, and upon issues in evaluating large-scale digital initiatives with reference to constructs and methods utilised in UK national initiatives which are concerned with networked learning. Building blocks towards an evaluation framework for large scale national digital initiatives which are related to networked learning are identified.